PERAN PROTEIN MEMBRAN LUAR 55 kDa Salmonella typhi ISOLAT JEMBER SEBAGAI PROTEIN HEMAGLUTININ DAN ADHESIN - Diana Chusna Mufida; Candra Bumi; Heni Fatmawati (The East Java Biological Society, 2009)
Salmonella typhi is an obligate pathogen that is usually found in clinical specimen from typhoid fever patients. The pathogenic mechanism of bacteria are not fully elucidated especially its potential activity of the outer membrane protein (OMP) as hemaglutinin and adhesion molecule. After identification, bacterial isolate of outer membrane protein fraction 12,5% SDS-PAGE were used to isolate OMP followed by hemaglutinin test and in vitro adhesion test. The study showed that the 55 kDa protein of S. typhi is a hemaglutinin protein that could agglutinate, Wistar mouse erythrocytes. The 55 kDa OMP is also an adhesion protein showed by its activity to adherence to Wistar mice’s enterocyt. The increased dose of 55 kDa OMP will decrease the amount of S. typhi bacteria adherenced to Wistar mice’s enterocyt. Outer membrane protein 55 kDa S. typhi as hemagglutinin and also adhesion protein.